2021
DOI: 10.1055/s-0041-1736339
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Perioperative Medication-Related Clinical Decision Support Tool to Prevent Medication Errors: An Analysis of User Feedback

Abstract: Objectives Medication use in the perioperative setting presents many patient safety challenges that may be improved with electronic clinical decision support (CDS). The objective of this paper is to describe the development and analysis of user feedback for a robust, real-time medication-related CDS application designed to provide patient-specific dosing information and alerts to warn of medication errors in the operating room (OR). Methods We designed a novel perioperative medication-related CDS app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…18 Previous studies have demonstrated the importance of analyzing user needs while designing CDS and other electronic tools. 19,20…”
Section: Methods Study Designmentioning
confidence: 99%
“…18 Previous studies have demonstrated the importance of analyzing user needs while designing CDS and other electronic tools. 19,20…”
Section: Methods Study Designmentioning
confidence: 99%
“…Even though experts may go wrong, they can learn from the rationale behind the correct decision and can revise their knowledge easily. 29…”
Section: Methodsmentioning
confidence: 99%
“…Even though experts may go wrong, they can learn from the rationale behind the correct decision and can revise their knowledge easily. 29 In the health care domain, experts will differ in their level of knowledge, experience, understanding and beliefs. Based on their thought process and cognition levels, each expert assigns a preference-weight value which ranges from one to 10 corresponding to 10 different attributes with respect to each alternative.…”
Section: Analysis On Experts' Preferencesmentioning
confidence: 99%
“…Over the past two decades, as electronic health record (EHR) adoption has increased, so has the volume of electronic patient data that clinicians can access at the point of care, and use to support treatment decisions. [1][2][3][4] Computerized clinical decision support can facilitate user interaction with these data to visualize trends and prompt clinical action. [5][6][7][8] Yet, the proliferation of EHRs and electronic clinical information has also led some to describe the information environment in primary care settings as "chaotic" and potentially harmful to clinician decision making and stress levels.…”
Section: Background and Significancementioning
confidence: 99%